Novel Erwinia persicina Infecting Phage Midgardsormr38 Within the Context of Temperate Erwinia Phages - Zrelovs, Nikita; Dislers, Andris; Kazaks, Andris (Frontiers in Microbiology, 2020)
Prophages or prophage remnants are found in chromosomes of many bacterial strains and might increase the environmental fitness and/or virulence of their hosts. Up to this date complete genome sequences of only seven temperate bacteriophages infecting bacteria from genus Erwinia, comprising of mostly phytopathogenic bacteria, are available publicly. No attempts to analyze the global diversity of temperate Erwinia phages and establish relationships between cultured temperate Erwinia phages and prophages were yet made. In this study we have isolated, sequenced and described novel Erwinia persicina infecting bacteriophage “Midgardsormr38”, as well as placed it in the context of previously described Erwinia sp. temperate phages and putative prophages derived from chromosomes of publicly available complete genomes of Erwinia sp. to broaden and investigate diversity of temperate Erwinia phages based on their genomic contents. The study revealed more than 50 prophage or prophage remnant regions in the genomes of different Erwinia species. At least 5 of them seemed to be intact and might represent novel inducible Erwinia phages. Given the enormous bacteriophage diversity, attempts to establish evolutionary relationships between temperate Erwinia phages revealed at least five different clusters of temperate phages sharing higher degree of similarity.